PELAKSANAAN PENDIDIKAN DAN PELATIHAN PEGAWAI APARATUR SIPIL NEGARA DI LINGKUNGAN SEKRETARIAT DAERAH KOTA PEKANBARU - sari, fara merian (Jurnal Niara, 2018)
The purpose of this research is to know the Implementation of Education and Training of State Apparatus of State Apparatus (ASN) in Pekanbaru City Regional Secretariat Year 2016 and Barriers Factor in Implementation of Education and Training of State Apparatus (ASN) in Pekanbaru City Regional Secretariat 2016. Based on the results of research on the implementation of Education and Training Method On The Job Site conducted in the Regional Secretariat of Pekanbaru In practice used the method of Debriefing, Job Rotation, Apprenticeship and Assignment While using methods of Information Presentation Techniques and Simulation Techniques, As for factors that become obstacles in the implementation of education and training (Training) Employees of State Civil Apparatus in the Regional Secretariat of Pekanbaru (1) It is not easy to obtain experienced staff from within because of the limited ability or time. (2) The number of participants must meet a favorable ratio. (3) The difficulty of arranging study time, meaning many things to consider. (4) experienced staff (senior) lack of encouragement or encouragement to new employees, so that when the learning begins the atmosphere is not conducive and the employees tend not to be passionate to follow the Training. (5) Participants may not directly apply the knowledge or skills gained from the exercise. (6) The cost is relatively larger than the cost if the exercise is held by the agency itself